PENGARUH IKLIM ORGANISASI TERHADAP TURNOVER INTENTION DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI - Maha Putra, Kadek Bayu Satrio; Suwandana, I Gusti Made (E-Jurnal Manajemen, 2017)
Job satisfaction is an important thing in a company in order to suppress the rise of turnover intention by considering the organizational climate as forming aspects of job satisfaction. The higher level of job satisfaction and organizational climate levels, the lower level of turnover intention of employees in the company. The purpose of this study to determine the influence of organization climate on turnover intention and job satisfaction as a mediating variable. The study was conducted at PT BFI Finance Indonesia Tbk. The study population as many as 78 people, using the technique of saturated samples. Data collection methods used were observation, interviews, and questionnaires. Data obtained with questionnaires were analyzed using the technique of path analysis (path analysis). The results of this study indicate that the organizational climate positive and significant effect on employee job satisfaction, organizational climate a significant negative effect on turnover intention of employees, job satisfaction a significant negative effect on turnover intention of employees, as well as job satisfaction significant negative effect in mediating between organizational climate on turnover intention.
Keywords: organizational climate, job satisfaction, turnover intention